(untitled) (REMUNOM, 2026)
Pure (BaWO4) and erbium-doped (Ba0,99Er0,11WO4) barium tungstate nanocrystals were tested as heterogeneous photocatalysts for the degradation of the cationic dye methylene blue under sunlight. The synthesis of these materials was carried out using the chemical precipitation method at room temperature, and the materials were characterized by X-ray diffraction and scanning electron microscopy. When investigating their photocatalytic efficiencies, Ba0,99Er0,11WO4 was considered more efficient for dye removal within the first 60 minutes. After this period, it was found that the BaWO4 photocatalyst was the most efficient, enabling a 68.8% removal rate after 210 minutes. Both materials showed satisfactory photocatalytic efficiency under the experimental conditions and are promising for environmental applications, such as the degradation of textile effluents.